2012
DOI: 10.1208/s12248-012-9405-y
|View full text |Cite
|
Sign up to set email alerts
|

Semi-mechanistic Modeling of the Interaction Between the Central and Peripheral Effects in the Antinociceptive Response to Lumiracoxib in Rats

Abstract: Abstract. The model-based approach was undertaken to characterize the interaction between the peripheral and central antinociceptive effects exerted by lumiracoxib. The effects of intraplantar and intrathecal administrations and of fixed ratio combinations of lumiracoxib simultaneously administered by these two routes were evaluated using the formalin test in rats. Pain-related behavior data, quantified as the number of flinches of the injected paw, were analyzed using a population approach with NONMEM 7. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this regard, oral and spinal co-administration of diclofenac produced an additive interaction (Ortiz et al ., 2008), while the intraperitoneal and intraplantar co-administration of tramadol, produced a self-synergistic antinociceptive effect (Pozos-Guillén et al ., 2006). Furthermore, it has been proposed that the antinociceptive effect after intraplantar and intrathecal co-administration of lumiracoxib is additive (Vélez de Mendizábal et al ., 2012) in the formalin test. In the present study, although the mechanisms underlying the additive effect of ketorolac or paracetamol and the self-synergism of indomethacin were not explored, it is likely that the above-cited peripheral and central mechanism dependent and independent of COX inhibition are involved.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, oral and spinal co-administration of diclofenac produced an additive interaction (Ortiz et al ., 2008), while the intraperitoneal and intraplantar co-administration of tramadol, produced a self-synergistic antinociceptive effect (Pozos-Guillén et al ., 2006). Furthermore, it has been proposed that the antinociceptive effect after intraplantar and intrathecal co-administration of lumiracoxib is additive (Vélez de Mendizábal et al ., 2012) in the formalin test. In the present study, although the mechanisms underlying the additive effect of ketorolac or paracetamol and the self-synergism of indomethacin were not explored, it is likely that the above-cited peripheral and central mechanism dependent and independent of COX inhibition are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a self-synergism was reported with WIN 55,212-2 administered in two different routes, the intrathecal and intraplantar [ 4 ]. However, other studies have only shown an additive effect [ 5 ], or there was no change in the antinociceptive effect with the administration of tramadol by two different routes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%